Traffic Accidents in Switzerland: How Hazardous are "High Risk" Groups? An Analysis Based on Police Protocols - Thomas Gautschi; Dominik Hangartner; Aline Bütikofer (Swiss Journal of Economics and Statistics, 2007)
By January 1, 2005, Switzerland reduced the legal level of blood–alcohol concentration while driving from 0.8h to 0.5h. This happend on basis of the assumptions that more restrictive per mil levels increase road safety. The benefit of lower blood–alcohol levels, however, depends on whether drinking drivers indeed pose a risk for themselves and other road users. Analyses using official data of all 84'437 two–car crashes during 2001–2005 indeed show a higher relative risk of drinking to sober drivers. And, we also find evidence that prejudices against drivers with an Eastern European citizenship, contrary to recent newspaper articles, are groundless.
Keywords: C51; C81; K41; R41; 330; Traffics accidents; drinking; statistical modelling; estimation of risk